Implementation of the Bsps (Self-Help Housing Stimulus Assistance) Program Policy in Jatisari Village, Cisompet District, Garut Regency - Mulyaningsih; Ade Burhanudin; Sopa Siti Marwah; Yagus Triana (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
The problem of uninhabitable housing remains a major challenge in rural areas, including in Jatisari Village, Cisompet District, Garut Regency, where the majority of the population is classified as low-income. Limited economic conditions make it difficult for the community to provide adequate housing independently. To address this problem, the government implemented the Self-Help Housing Stimulant Assistance Program (BSPS) as an effort to improve housing quality through stimulus assistance combined with the principle of community self-reliance. However, in practice at the village level, the BSPS program still faces various obstacles that can affect the effectiveness of achieving policy objectives. This study aims to analyze the implementation of the BSPS Program policy in Jatisari Village, Cisompet District, Garut Regency. The study used a descriptive qualitative approach with a case study method. Data collection was conducted through in-depth interviews, field observations, and documentation studies, with informants consisting of village officials, BSPS facilitators, and community beneficiaries. Data analysis was carried out through the process of data reduction, data presentation, and drawing conclusions, while the validity of the data was tested using source and technique triangulation. The results of the study indicate that the implementation of the BSPS Program in Jatisari Village has been running and has provided real benefits in improving the quality of uninhabitable houses. Supporting factors for program implementation include village government support, active community participation, and technical assistance from BSPS facilitators. Meanwhile, inhibiting factors found include limited aid budget, low understanding of some community members regarding program mechanisms, delays in material procurement, and the economic conditions of aid recipients that limit their ability to self-help. This study concludes that the implementation of the BSPS Program policy in Jatisari Village is quite successful, but not yet fully optimal, so it is necessary to improve the quality of socialization, strengthen resources, and coordinate between parties so that program implementation at the village level can be more effective and sustainable.